2020
DOI: 10.1044/2020_aja-19-00077
|View full text |Cite
|
Sign up to set email alerts
|

Sentence-Based Experience Logging in New Hearing Aid Users

Abstract: Purpose The aim of this study was to develop a tool to gain insight into the daily experiences of new hearing aid users and to shed light on aspects of aided performance that may not be unveiled through standard questionnaires. Method The tool is developed based on clinical observations, patient experiences, expert involvement, and existing validated hearing rehabilitation questionnaires. Results An online t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The number of studies excluded for each reason for exclusion is shown in Figure 1 . For example, 18 studies appeared to meet the inclusion criteria, but after full-text reviewing, they were excluded as they were not truly qualitative or did not contain qualitative data (e.g., Leek et al, 2008 ; Lund et al, 2020 ; Solheim et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies excluded for each reason for exclusion is shown in Figure 1 . For example, 18 studies appeared to meet the inclusion criteria, but after full-text reviewing, they were excluded as they were not truly qualitative or did not contain qualitative data (e.g., Leek et al, 2008 ; Lund et al, 2020 ; Solheim et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the patients will be tested with a subset of the tests presented here, fitted with hearing aids, and their aided performance and self-perceived benefit were evaluated in and out of the clinic. This is expected to set the basis for targeted interventions involving not only hearing-aid fitting, but also the use of new tools for evaluating the experiences of hearing-aid users (Lund et al, 2020 ) and recommendations for individualized pathways (Sanchez-Lopez et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…These insights can also be useful for recreating the important situations in a clinical environment and then evaluate the improvement by means of aided performance tests. In cases with handicap priorities in their profile, the participation restrictions can be evaluated using measures out of the clinic that can capture the user positive and negative experiences in daily life (Lund et al 2020). One last important factor that can be part of this personalized hearing healthcare is to gather information about the auditory ecology of the patient (Gatehouse et al, 2003) which could be captured by the active responses of the patient (ecological momentary assessments; e.g., Holube et al, 2020; Smeds et al, 2020) or their hearing devices (Christensen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%